1988
DOI: 10.1017/s0141347300008478
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Different Combinations of Continuous and Partial Reinforcement Schedules on Response Persistence in Mentally Handicapped Children

Abstract: Two experiments investigated the effects on persistence of behaviour in extinction of different training procedures, using mentally handicapped boys who were trained to place objects of different shapes into matching holes in a box for sensory reinforcers. In Experiment 1 two subjects were given three training procedures: (i) a C-C procedure, consisting of 80 trials of continuous reinforcement (CRF); (ii)a P-P procedure, consisting of 80 trials of variable ratio reinforcement (VR5); and (iii) a C-P procedure, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1992
1992
1992
1992

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…There exists a wide variety of research data which suggests that once continuous reinforcement is withdrawn, the acquired behaviour quickly extinguishes (Kazdin & Polster, 1973;Koegel & Rincover, 1977; Kazdin, 1984). Although it has been advocated that, as soon as a behaviour is acquired on a CRF schedule, reinforcement should be switched to an intermittent schedule, there have been a number of difficulties with this procedure (Tierney & Smith 1988; Dehn, 1969). Dehn (1969) found that the smoothness of transfer from continuous to intermittent schedules is a key factor in the success of the procedure.…”
Section: Reinforcementmentioning
confidence: 99%
See 1 more Smart Citation
“…There exists a wide variety of research data which suggests that once continuous reinforcement is withdrawn, the acquired behaviour quickly extinguishes (Kazdin & Polster, 1973;Koegel & Rincover, 1977; Kazdin, 1984). Although it has been advocated that, as soon as a behaviour is acquired on a CRF schedule, reinforcement should be switched to an intermittent schedule, there have been a number of difficulties with this procedure (Tierney & Smith 1988; Dehn, 1969). Dehn (1969) found that the smoothness of transfer from continuous to intermittent schedules is a key factor in the success of the procedure.…”
Section: Reinforcementmentioning
confidence: 99%
“…Research carried out with children with learning disabilities (Tierney & Smith, 1988), demonstrated that responding on an intermittent schedule during the maintenance phase of a training programme was more likely if initial response acquisition was programmed using a partial schedule than if response acquisition was initially programmed using a CRF schedule and then switched to an intermittent schedule (Tierney & Smith, 1988). This suggests that even from the beginnings of teaching a discrimination, not all correct responses should be reinforced if optimal response generalisation is to be attained.…”
Section: Reinforcementmentioning
confidence: 99%